Cabrini [videorecording (DVD)] - Monteverde, Alejandro; Barr, Rod; Dell'Anna, Cristiana; Morse, David, 1953-; Maggiora, Romana; Ielapi, Federico; Bocelli, Virginia; Villazón, Rolando; Giannini, Giancarlo; Lithgow, John, 1945-; Back, Gene (Angel Studios, 2024)
Based on the true story of the life and times of Francesca Cabrini, recounting Cabrini's experiences arriving as an Italian immigrant in New York City in 1889, witnessing the living conditions of the city's poor, and taking on the city's mayor to improve living and healthcare conditions for all.